2009
DOI: 10.1007/bf03080134
|View full text |Cite
|
Sign up to set email alerts
|

How power and trust explain procedural fairness effects on self-esteem

Abstract: When authorities enact procedures in a fair manner, they positively influence their followers' self-esteem. Building on fairness heuristic theory and sociometer theory, we predicted that this effect is mediated by trust in the authority because procedural fairness heightens trust as an indicator of a valued relationship with an authority who will protect followers' interests. Trust should, subsequently, heighten followers' self-esteem as an indicator of their value to the organisation. Further, we expected thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The first paper by Langendijk, van Dijke, and De Cremer (2009) sets out to show why fairly enacted procedures enhance followers' self-esteem by addressing the role of authority power in this process. They show that particularly high power authorities are effective in enhancing follower self-esteem, presumably because high power makes the authority more effective in influencing follower status (e.g., by promoting or, conversely, excluding the employee from the organisation).…”
mentioning
confidence: 99%
“…The first paper by Langendijk, van Dijke, and De Cremer (2009) sets out to show why fairly enacted procedures enhance followers' self-esteem by addressing the role of authority power in this process. They show that particularly high power authorities are effective in enhancing follower self-esteem, presumably because high power makes the authority more effective in influencing follower status (e.g., by promoting or, conversely, excluding the employee from the organisation).…”
mentioning
confidence: 99%
“…As outlined previously, a study of majority and minority groups' relative attention to procedural justice in a new democracy (Tanzania), found support for the relational model of procedural justice, showing that less powerful minority groups cared more about relational concerns in support for the incumbent government than powerful majority groups (Epstein et al, 2013). Related research has found evidence that fairness cues are particularly salient for minority group members, who look to authorities for information about their group's social standing (Huo, Binning, & Molina, 2010b;Huo & Molina, 2006;Langendijk, Van Dijke, & De Cremer, 2009). This research suggests that low-power citizens are more likely to use process information in formulating support for authorities (Tyler & Lind, 1992), as attending to procedural justice cues resolves any uncertainty about a minority group's standing in the larger society.…”
Section: Powermentioning
confidence: 99%